Optical studies of cubic III-nitride structures - Powell, Ross E L (2014)
The properties of cubic nitrides grown by molecular beam epitaxy (MBE) on GaAs (001) have been studied using optical and electrical techniques. The aim of these studies was the improvement of the growth techniques in order to improve the quality of grown nitrides intended for bulk substrate and optoelectronic device applications. We have also characterised hexagonal nanocolumn structures incorporating indium. Firstly, bulk films of cubic AlxGa1-xN with aluminium fractions (x) spanning the entire composition range were tested using time-integrated and time-resolved photoluminescence (PL) plus reflectivity measurements. Strong PL emission was recorded from the samples, with improved intensity for higher aluminium concentrations. Temperature dependent and time-resolved PL showed the increasing role of carrier localisation at larger AlN fractions. The reflectivity results showed a near-steady increase in the bandgap energy with increasing AlN content. Alternative interpretations that did and did not involve a transition from direct-gap to indirect-gap behaviour in cubic AlxGa1-xN were considered. We next looked at cubic AlxGa1-xN/GaN/AlxGa1-xN single quantum well (QW) structures with varying AlN content in the barrier regions. The PL studies indicated that carrier escape from the QWs and non-radiative recombination at layer interfaces were limiting factors for strong well emission. Higher AlN concentration in the barriers appeared to exacerbate these problems. The doping of cubic GaN with silicon (n-type) and magnesium (p-type) was also studied. For Mg-doped GaN, a strong blue band emission was noted in the PL spectrum, which became more intense at higher doping levels. The Mg-doped GaN layers had low conductivity and their mobility could not be measured due to strong compensation effects. The cubic film had similar time-resolved PL properties for the blue band emission compared to hexagonal Mg:GaN. These results suggested that the blue band was the result of recombination between a shallow Mg acceptor and deep donor, believed to be a complex including a nitrogen vacancy and an Mg atom. This complex was also associated with the compensation effect seen in the electrical measurements. With the Si-doped cubic GaN, we observed PL spectra that were consistent with other sources. Thicker layers of GaN:Si did not have measurable mobility. This was likely caused by the rough surface structure that was imaged using a scanning electron microscope. The thin layer had a very smooth surface in comparison. The mobility of sub-micron thickness layers with a carrier concentrations of n = 2.0×1018cm-3 and n = 9.0×1017cm-3 were μ = 3.9cm2/Vs and μ = 9.5cm2/Vs respectively. The mobility values and structural issues indicated that growth improvements were needed to reduce scattering defects. In addition to cubic structures, we have considered nanocolumn growth of InGaN and InN. InxGa1-xN nanocolumns were grown on Si (111) by MBE with a nominal indium concentration of x = 0.5. PL emission was obtained from samples grown at higher temperature, but overall intensity was low. A second set of samples, where nanocolumn growth was followed by growth of a continuous coalesced film exhibited much stronger PL emission, which was attributed to the elimination of a phase separated core-shell structure in the nanocolumns. Next, a coalesced InxGa1-xN structure with vertically varying indium fraction was characterised. PL readings showed evidence of successful concentration grading. Finally, the PL spectra of coalesced InN layers were recorded, for which a specialised infrared PL system needed to be used. The results highlighted how increased growth temperature and indium flux can improve PL properties. For the binary alloy however, coalescence growth can decrease PL intensity compared to the nanocolumns stage.